2023
DOI: 10.1038/s41564-022-01313-7
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobacterium tuberculosis protein O-phosphorylation landscape

Abstract: Protein phosphorylation is a main mechanism for translating extracellular signals into cellular adaptations. In bacteria, the two-component system has been the paradigm of protein phosphorylation. Increasingly, however, protein serine/threonine and tyrosine phosphorylation (O-phosphorylation) mediated by serine/threonine protein kinases (STPKs) is identified. Mycobacterium tuberculosis (Mtb) in particular has a larger repertoire of both STPKs and O-phosphoproteins than most bacteria, suggesting a more prevalen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 131 publications
(135 reference statements)
1
12
0
Order By: Relevance
“…M. tuberculosis could dephosphorylate MenT3 in vitro (Yu et al , 2020). Reversibly, a fraction of free active MenT3 could also be affected by endogenous Ser/Thr protein kinases (STPKs) like PknD and PknF (Frando et al , 2023), suggesting that the level of active endogenous MenT3 toxin might not solely be controlled by the antitoxin, but also by responsive endogenous kinase/phosphatase networks to ensure translational control is attuned to physiological need during growth and infection.…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis could dephosphorylate MenT3 in vitro (Yu et al , 2020). Reversibly, a fraction of free active MenT3 could also be affected by endogenous Ser/Thr protein kinases (STPKs) like PknD and PknF (Frando et al , 2023), suggesting that the level of active endogenous MenT3 toxin might not solely be controlled by the antitoxin, but also by responsive endogenous kinase/phosphatase networks to ensure translational control is attuned to physiological need during growth and infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that M. tuberculosis is equipped with distinct eukaryotic-like protein kinases (32, 33) and that TakA has very little similarity with these proteins, thus providing the rationale to investigate the role of STPKs in the regulation of TA modules. During the preparation of this manuscript, Frando et al, reported widespread O -phosphorylation of the M. tuberculosis H37Rv proteome (48). While their data implicated multiple STPKs in TA regulation, this study is the first instance that provides direct biochemical evidence of post-translational modification of mycobacterial Type II Rel TA modules via PknK highlighting a novel underlying regulatory mechanism to modulate TA function.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies are beginning to revise this view. The number of phosphosites identified in MS-based studies is climbing sharply, with several recent studies showing pervasive O -phosphorylation ( 14 22 ) ( Fig. 1 ).…”
Section: The Evolving View Of Bacterial Protein Phosphorylationmentioning
confidence: 91%
“…1 ). In fact, in Mycobacterium tuberculosis ( Mtb ), a degree of phosphorylation that is on par with O -phosphorylation in eukaryotes has recently been identified ( 14 ) ( Fig. 1 ).…”
Section: The Evolving View Of Bacterial Protein Phosphorylationmentioning
confidence: 99%